Financial Crises and Recovery Trajectories: A Comparative Panel Study of Crisis Types and Recovery Dynamics - Piepers,Jelien (2025)
This paper examines the economic consequences of financial crises and the determinants of recovery duration through a structural-institutionalist perspective. Drawing on cross-country data from 160 countries (1950–2019) and using updated classifications of crisis episodes, it explores two central questions: how do different types of crises affect GDP per capita? and what factors explain variation in recovery time? Results from fixed-effects regressions suggest that sovereign debt crises have the most damaging effect on income levels, while banking and currency crises have effects only on growth patterns. The time-to-event models show that the likelihood and trajectories of recovery are not solely crisis-driven but partly shaped by institutional and macroeconomic factors. These effects are on average more decisive in emerging markets, where state capacity is limited. This research provides new empirical insights into how crisis type and structural fundamentals shape economic resilience and offers critical insights for designing post-crisis recovery strategies.
Keywords: Crisis; Recovery Time; Institutions; Emerging/Advanced